Botanical Assessments of High-Quality Southern Shrub-Carr and Hardwood Swamp Wetlands in the Undeveloped Lowell Regional Greenspace, Kent County, Michigan - Carolyn R. Koehn; David P. Warners; Garrett E. Crow; Haley R. Weesies; Jonathan D. Walt; Zachary E. Hartwig (The Great Lakes Botanist)
The 2019–2023 Masterplan for Kent County Parks includes the future development of acquired properties that have been designated as the Lowell Regional Greenspace (528 acres), occupying nearly the entirety of Section 22 of Lowell Charter Township in Kent County, Michigan. Four wetlands located in the same drainage basin along Karen Creek in the Lowell Regional Greenspace were inventoried for floristic quality assessments during the summers of 2016, 2018, 2019, and 2021. One of the wetlands was forested and determined to be a southern hardwood swamp community type. The other three wetlands are best classified as shrub-carr communities. In the southern hardwood swamp, we recorded 94 species, of which 87 (92%) are native. A total of 321 species were documented in the three shrub-carrs wetlands combined. The number of species in each shrub-carr site, ranging from 172 to 238, is roughly twice that for the southern hardwood swamp site. Two of the species documented are listed as Special Concern in Michigan, and two are new county records for Kent County, Michigan. A non-metric multidimensional scaling model (NMDS) was run to spatially compare similarities and differences among the sites. The Sørensen Index of Similarity, which was employed to further discern differences between pairs of individual sites, was also useful for assigning plant community types as described by the Michigan Natural Features Inventory (2016). The Floristic Quality Assessments indicate that all four of the wetlands are floristically important statewide; furthermore, the three shrub-carr communities have exceptional conservation value. We discovered that the three shrub-carr sites have a high degree of similarity in their species assemblages, whereas the southern hardwood swamp was markedly different. The high richness and significant floristic quality of the shrub-carr sites highlight the conservation value of these often-overlooked habitats. This study underscores the importance of preserving even small tracts of persisting remnant natural habitats. Our research should be of use to Kent County Parks as they approach development of the Lowell Regional Greenspace into a multiple-use recreational space, as well as to those interested in learning more about how to assess and compare habitat quality of remnant natural areas.